Critical comparison on investment of Takaful funds in family takaful; a case study of PT. Asuransi Takaful Keluarga, and Takaful Ikhlas Sdn. Bhd. - Razali, Siti Salwani; Yulisia, Cynthia Suci Ayu (2010)
The increasing awareness of people to transfer and share risk through takaful has made takaful to become an important element of Islamic financial institution. As we know, insurance is a conventional financial system that is free to invest their funds in any financial instrument, without any halal and haram restrictions. In the context of conventional insurance, the insurance company normally invests its funds into conventional investment instruments that generate interest (riba) income. Takaful serves as an alternative islamically accepted mode of mitigating risk. Takaful has becoms one of the wealth management instrument in Indonesia and Malaysia that is based on shariah injunction. To fulfill this concept, Takaful is required to give priority to the practices and activities that does not contradict the concept of Takaful itself that is based on the injunction of Al-Quran and Sunnah. In participant point of view, Takaful operator is expected to be more cooperative (ta’awuniyah) oriented rather than profit maker. However, Takaful operator is expected to generate income by investing some proportion of the fund based on Shariah compliant investment instruments. Therefore, the purpose of this study is to investigate the investment activities of Takaful funds in Indonesia and Malaysia with critical comparison of investment and operational process of two Family Takaful Companies, namely PT. Asuransi Takaful Keluarga in Indonesia and Takaful Ikhlas Sdn. Bhd In Malaysia. The significance of this study is to know the activities of Takaful Companies in Indonesia and Malaysia in terms of contract they use, process of investing the funds, and distribution of surplus underwriting.